ANALISIS TINGKAT KEBUGARAN SISWA SEKOLAH LUAR BIASA DALAM MENGHADAPI KONDISI BENCANA - Andi Ariyandy; Ami Febriza Achmad; Nuralam Sam; Irianto Kadir; Muhammad Phetrus Johan; Muhammad Awal; Andi Ainun Zulkiah Surur; Nindrahayu Nindrahayu; Andi Irwan Muluk; Arianti Arianti (LPPM Universitas Bina Bangsa, 2023)
Children with disabilities are a part of the vulnerable group in disaster situations, so they need to be provided with training to increase their capacity to deal with disasters. In addition, this community service activity was also doing with socialization for teacher, stakeholders, parents, and students of the SLB YPAC Makassar City. This activity aims to increase knowledge, understanding, and capacity building for children with disabilities, teachers and stakeholders at service activity locations. The activity methods used are health education, video screenings, question and answer sessions, and direct measurements related to anthropometry, vital signs and physical capacity in YPAC SLB students. This activity was carried out in 3 stages, the first stage was assessment and observation of the school environment where the service was held. The second stage is the implementation of core activities which include educational activities, outreach to demonstrations. In the third stage, an evaluation of activities was carried out on applying empathetic communication to teachers and an increase in knowledge related to disaster management measures after socialization and education. Apart from that, educational videos were also handed over and tools related to disaster mitigation were delivered at SLB YPAC Makassar city. The results obtained from this activity are increasing knowledge regarding empathetic communication techniques and first aid when faced with a disaster situation for children with disabilities, teachers, and stakeholders at SLB YPAC Makassar City